Gravettian hand stencils as sign language formatives - Etxepare, Ricardo (Philos Trans R Soc Lond B Biol Sci, 2021)
Several Upper Palaeolithic archaeological sites from the Gravettian period display hand stencils with missing fingers. On the basis of the stencils that Leroi-Gourhan identified in the cave of Gargas (France) in the late 1960s, we explore the hypothesis that those stencils represent hand signs with deliberate folding of fingers, intentionally projected as a negative figure onto the wall. Through a study of the biomechanics of handshapes, we analyse the articulatory effort required for producing the handshapes under the stencils in the Gargas cave, and show that only handshapes that are articulable in the air can be found among the existing stencils. In other words, handshape configurations that would have required using the cave wall as a support for the fingers are not attested. We argue that the stencils correspond to the type of handshape that one ordinarily finds in sign language phonology. More concretely, we claim that they correspond to signs of an ‘alternate’ or ‘non-primary’ sign language, like those still employed by a number of bimodal (speaking and signing) human groups in hunter–gatherer populations, like the Australian first nations or the Plains Indians. In those groups, signing is used for hunting and for a rich array of ritual purposes, including mourning and traditional story-telling. We discuss further evidence, based on typological generalizations about the phonology of non-primary sign languages and comparative ethnographic work, that points to such a parallelism. This evidence includes the fact that for some of those groups, stencil and petroglyph art has independently been linked to their sign language expressions. This article is part of the theme issue ‘Reconstructing prehistoric languages’.